2019
DOI: 10.7554/elife.50054
|View full text |Cite
|
Sign up to set email alerts
|

Cue-inhibited ventrolateral periaqueductal gray neurons signal fear output and threat probability in male rats

Abstract: The ventrolateral periaqueductal gray (vlPAG) is proposed to mediate fear responses to imminent danger. Previously we reported that vlPAG neurons showing short-latency increases in firing to a danger cue – the presumed neural substrate for fear output – signal threat probability in male rats (Wright et al., 2019). Here, we scrutinize the activity vlPAG neurons that decrease firing to danger. One cue-inhibited population flipped danger activity from early inhibition to late excitation: a poor neural substrate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Our laboratory has observed robust danger, uncertainty, and safety discrimination using suppression ratios calcluated from rates of rewarded nose poking 31,32,[35][36][37] . Classic studies examining defensive behaviour have reported robust post shock freezing 18,25,38 .…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory has observed robust danger, uncertainty, and safety discrimination using suppression ratios calcluated from rates of rewarded nose poking 31,32,[35][36][37] . Classic studies examining defensive behaviour have reported robust post shock freezing 18,25,38 .…”
Section: Resultsmentioning
confidence: 99%
“…The different types of vlPAG responses to the CS that we observed are consistent with previous reports: the fast onset neurons 10, 12, 36, 44 (our cluster 1) likely encode the fear prediction error 42, 44 and shall correspond, at least in part, to dopamine-vGluT2 expressing neurons 42 . Slower excitatory responses (our cluster 3) rather encode threat probability 12, 44 , while neurons with inhibitory responses to the CS (our cluster 2) more likely encode fear expression 10, 45 .…”
Section: Discussionmentioning
confidence: 98%
“…So far, no differences in VP activity/function have been found in studies that examined biological sex 18,39,55 . Our laboratory has observed complete and comparable fear discrimination in male and female rats 11,51,56,57 . We predict that equivalent relative threat signaling will be observed in female and male VP neurons.…”
Section: Cue-excited Neurons Increase Firing To Rewardmentioning
confidence: 89%
“…Regression output was a beta coefficient for each regressor, quantifying the strength (greater distance from 0 = stronger) and direction (>0 = positive and <0 = negative) of the predictive relationship between each regressor and single unit firing. Regression allowed us to determine whether the firing of each VP neuron was better described by the rat's behavior in that session (fear output) or the shock probability associated with each cue (relative threat) 50,51 .…”
Section: Low and Intermediate Firing Neurons Signal Relative Threatmentioning
confidence: 99%